Febrile-range temperature modifies cytokine gene expression in LPS-stimulated macrophages by differentially modifying NF-κB recruitment to cytokine gene promoters - Cooper, Zachary A. (American Physiological Society, 2010)
We previously showed that exposure to febrile-range temperatures (FRT, 39.5–40°C) reduces LPS-induced TNF-α expression, in part through the direct interaction of heat shock factor-1 (HSF1) with the TNF-α gene promoter. However, it is not known whether exposure to FRT also modifies more proximal LPS-induced signaling events. Using HSF1-null mice, we confirmed that HSF1 is required for FRT-induced repression of TNF-α in vitro by LPS-stimulated bone marrow-derived macrophages and in vivo in mice challenged intratracheally with LPS. Exposing LPS-stimulated RAW 264.7 mouse macrophages to FRT reduced TNF-α expression while increasing IL-1β expression despite the two genes sharing a common myeloid differentiation protein-88 (MyD88)-dependent pathway. Global activation of the three LPS-induced signaling intermediates that lead to cytokine gene expression, ERK and p38 MAPKs and NF-κB, was not affected by exposing RAW 264.7 cells to FRT as assessed by ERK and p38 phosphorylation and NF-κB in vitro DNA-binding activity and activation of a NF-κB-dependent synthetic promoter. However, chromatin immunoprecipitation (ChIP) analysis demonstrated that exposure to FRT reduced LPS-induced recruitment of NF-κB p65 to the TNF-α promoter while simultaneously increasing its recruitment to the IL-1β promoter. These data suggest that FRT exerts its effects on cytokine gene expression in a gene-specific manner through distal effects on promoter activation rather than proximal receptor activation and signal transduction.